Erasing discourse identities of narrative hegemony Reading in the novel (The Virgin of Sinjar) by Ward Badr Al-Salem (Raparin Journal of Humanities (RJH), 2023)
This research is an attempt to study identity in the novel “The Virgin of Sinjar” by Ward Badr Al-Salem in the light of a group of rhetorical dominions that practiced erasing all its details and composition towards the Yezidi Kurds, especially that the space of the novel has considered the human component as the axis of the geology of the narrative text, and for this the novel came to bear these dominations through a series of narrative sequences that employed the discourse within the circle of erasure.The nature of the research required an introduction in which he explained why we chose this novel to be the sample of the research, and paved for him with a preamble in which I talked about identity representation, followed by two sections, the first section was called “Erasing the Yazidi Identity,” while the second section was marked “Erasing the Kurdish Identity.” Both sections included several manifestations, including a conclusion, and a list of sources and references for the research.This study is based on textual critical reading by tracing the applied procedures of cultural criticism revealing the manifestation of identity representations behind rhetorical dominions in the textual structures of the novel.